IDENTIFIKASI LAPISAN BAWAH PERMUKAAN MENGGUNAKAN METODE GEOLISTRIK DI SEKITAR REMBESAN LUMPUR DI DESA BAKUSTULAMA, KECAMATAN TASIFETO BARAT, KABUPATEN BELU - Sianturi, Hery Leo; Lau, Claudya Hendrika Putri; Johannes, Albert Zicko; Tanesib, Jehunias L. (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2025)
The study has been conducted to identify subsurface layers using the Wenner-Schlumberger geoelectric method. This research aims to understand the rock layering and hydrogeology at the research site. The research was conducted with a field survey on four 480-meter-long tracks in Bakustulama Village. Rock resistivity data was measured using a resistivity meter and analyzed using Res2DinV software to produce a 2D cross-sectional model. This method utilizes rock resistivity to determine the nature and layering of rocks in the subsurface, focusing on potentially water-saturated zones and fractures. The results show that the subsurface layer in Bakustulama Village consists of sandstone in the upper layer (0-20 meters) with medium resistivity (100-700 Ωm), followed by a highly water-saturated clay layer with low resistivity (0-100 Ωm), and a limestone layer with high resistivity (700-1000). The subsoil in the Bakustulama Area is diversely arranged, with sandstone layers at the surface to a depth of about 20 meters that suspected to have high porosity and are easily drained by water. Underneath, water-saturated clay layers are dominant and difficult for fluids to pass through.